Work Motivation, Competence, and Employee Performance in a Four-Star Hotel: Evidence from Bedrock Hotel Kuta Bali - Ari Maulana Yusro; Azmen Kahar (Pt. Threeple Herphi Educate, 2026)
The intensifying competition in Bali's four-star hotel segment requires sustained human-resource performance to maintain international service standards. This study examines the partial and simultaneous effects of work motivation and competence on employee performance at Bedrock Hotel Kuta Bali, where an internal appraisal indicated that the overall performance score rose from 10.6 (2024) to 11.9 (2025) while the competence sub-score remained stagnant at 3.0. A quantitative causal-associative design was employed using a saturated sample of 60 permanent employees. Data were collected through a five-point Likert questionnaire (29 items) adapted from established instruments and analysed using multiple linear regression in IBM SPSS Statistics 29. The instrument satisfied validity (r-count > 0.254) and reliability (Cronbach's α = 0.872–0.911), and all classical-assumption tests were met. The regression results show that work motivation (β = 0.390, t = 3.739, p < 0.001) and competence (β = 0.330, t = 3.247, p = 0.002) have positive and significant partial effects on employee performance, and jointly explain 31.9% of its variance (Adjusted R² = 0.295; F(2, 57) = 13.32, p < 0.001). Work motivation emerged as the more dominant predictor. The findings suggest that hotel management should implement department-specific competence-development programmes and motivation-enhancing practices—such as structured on-the-job training, supervisor coaching, and performance-based recognition—to sustain service quality during high-occupancy periods.